Impact of self-efficacy and peer support on academic stress at Ar-Rohmah Putri boarding school - Dyah Arbaini; Erwin Erlangga; Rini Sugiarti (Cendikia : Media Jurnal Ilmiah Pendidikan, 2026)
This study examined the effects of self-efficacy and peer support on academic stress among 12th-grade students at Ar-Rohmah Putri International Islamic Boarding School in Malang, Indonesia. A quantitative cross-sectional survey design was used, with proportional random sampling. Data were collected from 106 students using validated psychological scales and analyzed with multiple linear regression in IBM SPSS 29. Partial test results showed that self-efficacy (? = -0.147; p = 0.173) and peer support (? = -0.076; p = 0.481) did not significantly affect students' academic stress. Both variables also showed no significant combined effect on academic stress (F = 1.964; p = 0.145), with a coefficient of determination (R²) of 0.037, indicating that only 3.7% of the variance in academic stress was explained by these two variables. These findings suggest that academic stress among boarding school students is a complex phenomenon influenced by factors beyond self-efficacy and peer support, including academic workload, time management, coping strategies, and pressure from both school and family environments. Further research is recommended to identify other variables that may have a greater impact on academic stress levels in the boarding school context.